Detection of cellular redox reactions and antioxidant activity assays. (October 2017) - Meng, Dan; Zhang, Peng; Zhang, Lingling; Wang, Hong; Ho, Chi-Tang; Li, Shiming; Shahidi, Fereidoon; Zhao, Hui
Highlights: A comprehensive review of cellular antioxidant activity (CAA) measurements. Brief introduction of oxidation/reduction reaction in living cells. Cellular detection methods of reactive oxygen species (ROS). The importance of developing CAA assays with primary cells or in vivo assays. Abstract: Living organisms are continuously exposed to reactive oxygen species (ROS) during their lifespan. Small amounts of ROS can act as signal transduction molecules. However, excess ROS cause oxidative stress resulting in multiple adverse effects such as protein and lipid oxidation as well as DNA damage. Cells have developed an antioxidant defense system to maintain the balance between ROS production and scavenging, but imbalance often occurs leading to excess ROS. In this review, we summarized cellular redox reactions and their detection as well as cellular based assays that are used to measure and reflect the real case scenario of antioxidant potential of compounds of interest. Multiple cellular assays developed to evaluate the cellular levels of ROS and antioxidant activity were also reviewed. These studies lead to better understanding of redox homeostasis and identification of more natural antioxidant products that benefit human health.